Management of Adaptation of Organizational and Economic Mechanisms of Construction to Increasing Impact of Digital Technologies on the National Economy - Stetsenko, Sergii P.; Tytok, Viktoriya V.; Emelianova, Olena M.; Bielienkova, Olha Yu.; Tsyfra, Tetiana Yu. (Journal of Reviews on Global Economics, 2020)
Motivation: We note significant problems of developing countries, including Ukraine, with the adaptation of organizational and economic mechanisms of the construction industry to increase impact of digital technologies on their economic systems and construction sectors. Novelty: The scientific novelty is a set of management activities for the adaptation of organizational and economic mechanisms of Ukrainian construction companies to the development of digital technologies. Methodology and Methods: The research methods used in this study are a quantitative analysis of statistics on the dynamics of world GDP, the global construction industry, the construction industries of developing countries, including Ukraine, the global digital market, digital markets in developing countries, including Ukraine, for ten years using one-dimensional statistical methods (UT) based on random sampling. The paper also uses the correlation and regression analysis, namely the linear regression model, as well as the statistical verification of the obtained model by calculating the pair correlation coefficient, the coefficient of determination and the Chaddock scale in the study of the impact of digital technology development on the Ukrainian construction industry. Data and Empirical Analysis: To conduct the study, data were collected and an empirical analysis was conducted regarding the dynamics of world GDP, the world construction industry, the construction industries of developing countries, including Ukraine, the global digital market, digital markets in developing countries, including Ukraine, in 2009-2018 according to statistics from Knoema, The World Bank, Deloitte, State Statistics Service of Ukraine, UNCTAD, International Data Corporation, Gartner. Policy Considerations: The economy of the country and the construction sector requires development and implementation of a set of management activities to adapt organizational and economic mechanisms of construction in Ukraine to development of digital technologies.